SOME INFORMATION ABOUT THE DEVELOPMENT OF WHITE AND CHIPOR FISH IN ARTIFICIAL WATER RESERVOIRS OF SAMARKAND REGION (Euro-Asia Conferences, 2021)
The study examined the embryonic development of silver carp(Hypophthalmichthys molitrix) and bighead carp (Hypophthalmichthysnobilis Richardson, 1845), [1] which came to Uzbekistan fromreservoirs in China in the early 1960s. More than 10 genera of thisspecies have been studied locally. Embryonic development continuesnormally. At a water temperature of 21-23 ° C, embryos appear after 32hours, larvae undergo mixed feeding - after 4 days, exogenous feeding -after 5 days. Piglets reach sexual maturity at the age of 5-7 years andare fertilized in the summer. The female lays about 490-540 thousandpelagic eggs. Fertilization takes place in May-June at a watertemperature of 18-20 ° C.